2020
DOI: 10.1007/s10115-020-01462-3
|View full text |Cite
|
Sign up to set email alerts
|

A survey on context awareness in big data analytics for business applications

Abstract: The concept of context awareness has been in existence since the 1990s. Though initially applied exclusively in computer science, over time it has increasingly been adopted by many different application domains such as business, health and military. Contexts change continuously because of objective reasons, such as economic situation, political matter and social issues. The adoption of big data analytics by businesses is facilitating such change at an even faster rate in much complicated ways. The potential be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
0
9
0
8
Order By: Relevance
“…Nesse sentido, as redes sociais de mostram uma fonte de informações valiosa, onde as pessoas atualmente tendem a compartilhar seus pensamentos, emoções, sentimentos e preferências (Dinh, Karmakar, & Kamruzzaman, 2020, Thaichon et al, 2018. Além disso, é possível a obtenção dos dados do histórico de pesquisa do cliente (também conhecido por 'pegada digital') (Mero et al, 2020).…”
Section: Análise E Discussão Dos Resultadosunclassified
See 3 more Smart Citations
“…Nesse sentido, as redes sociais de mostram uma fonte de informações valiosa, onde as pessoas atualmente tendem a compartilhar seus pensamentos, emoções, sentimentos e preferências (Dinh, Karmakar, & Kamruzzaman, 2020, Thaichon et al, 2018. Além disso, é possível a obtenção dos dados do histórico de pesquisa do cliente (também conhecido por 'pegada digital') (Mero et al, 2020).…”
Section: Análise E Discussão Dos Resultadosunclassified
“…Mais que isso, métodos para extrair dados textuais e realizar análises de sentimentos possibilitam avaliações dinâmicas (Dinh et al, 2020). Tal que, o posicionamento da empresa na web não precisa ser estático e a distribuição do conteúdo ocorre em resposta a condição do lead (Mero et al, 2020;Syam & Sharma, 2018).…”
Section: Análise E Discussão Dos Resultadosunclassified
See 2 more Smart Citations
“…Context-aware innovations that make use of contextual data can enhance service customization driven by quality personalized feedbacks and objectives in service delivery which ultimately results in the adoption and diffusion of any technology such as m-government [178][179][180]. Mobile government context-aware services systems can empower context generation where information and services can be accessed via mobile devices based on location, people, or places of interest close by [181,182]. Again, our results showed that while mobile factor ubiquity was not significant in influencing the performance expectancy of mobile government services, it was however significant in determining both effort expectancy and intention to use mobile government services.…”
Section: Discussionmentioning
confidence: 99%